Shiga Toxin-Producing E. Coli O104:H4 Outbreak 2011 in Germany: Radiological Features of Enterohemorrhagic Colitis - Bannas, P.; Fraedrich, K.; Treszl, A.; Bley, T. A.; Herrmann, J.; Habermann, C. R.; Derlin, T.; Henes, F. O.; Wenzel, U.; Adam, G.; Yamamura, J. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: In 2011 a nationwide outbreak of Shiga toxin-producing E. coli (STEC) O104:H4 infection occurred in Germany with severe hemorrhagic colitis and hemolytic-uremic syndrome (HUS). We defined abdominal radiologic findings in these patients and correlated them with clinical parameters. Materials and Methods: 23 patients (7 men; age: 48 ± 19 years) with O104:H4 colitis and/or HUS received abdominal CT (n = 12) or radiographs (n = 11). Colonic distension, air-fluid levels, and free intraabdominal air were assessed. Colonic wall thickening, contrast enhancement, pericolic stranding, and ascites were evaluated on CT. Laboratory parameters and clinical presentation were reviewed. Chi-square test, Student’s t-test, McNemar’s test and Spearman correlation were performed. Results: Colonic lumen distension was seen in 16/23 patients (69.6 %). The ascending colon (11/23 patients; 47.8 %) and transverse colon (12/23 patients; 52.2 %) were dilated significantly more often (p = 0.006 and p = 0.003, respectively) than the descending colon (1/23; 4.3 %). All 12 patients undergoing CT scanning had abnormally thickened colonic wall segments, 3 (25 %) had pancolic involvement and 9 (75 %) had segmental involvement. The descending colon was predominantly affected (11/12 patients; 91.7 %) and thickened significantly more often than other colonic segments (p < 0.001). Conclusion: The segmental type of STEC O104:H4 colitis mainly affects the descending colon with upstream distension of the transverse/ascending colon and differs from other types of colitis.
Keywords: hemolytic-uremic syndrome; conventional radiography; CT; Shiga toxin-producing E. coli; O104:H4; enterohemorrhagic colitis